Aplicação de técnicas de cancelamento adaptativo de ruídos em equipamento de proteção auricular - Bergmann, Marcelo (2018)
The use of personal protective equipment (PPE) in the industry is mandatory for any situation of risk to the safety and health of the worker. Hearing protectors are used in noisy environments and have the function of preserving the auditory system. However, ther generate the sensation of acoustic isolation of the user in relation to the work environment. The general objective that is presented in this thesis is to solve the isolation situation, as well as, to propose improvements in hearing protectors to more effectively fulfill their protective role. Digital Signal Processing and Adaptive Noise Cancelling methodologies can be used to solve some of these issues and to provide a new concept in hearing protectors.